Insecticidal and nitrogen fixation activities of the transformed Paenibacillus polymyxa expressing Cry1C - IBRAHIM-HUSSIEN, AMAL; EL-GHAFFAR, NAHED IBRAHIM ABD; EL-SAYED HATEM, ADEL; ALDEBIS, HANI K.; VARGAS-OSUNA, ENRIQUE (Revista Colombiana de Entomología, 2011)
Laboratory tests have been conducted in order to ascertain the possibility of using the bacteria Paenibacillus polymyxa expressing the Bacillus thuringiensis Cry1C toxin as a delivery system for Cry proteins that can be used to control the Spodoptera littoralis noctuid on cotton crops. We have studied the insecticidal activity on first instar larvae of S. littoralis and the persistence of the transformed strain of P. polymyxa, compared with the unmodified strain and B. thuringiensis var. aizawai naturally expressing the toxin. the results show that the transformed bacteria was more toxic (LC50=7.04x107 spore+crystal/ml) than B. thuringiensis var. aizawai (LC50=8.47x107 spore+crystal/ml). High levels of persistence into foliar tissues and insecticide activity were found, at least until 720 hours after foliar treatment. On the other hand, its application in the plant increases the amount of nitrogen and improves soil nitrogenase activity compared to untransformed P. polymyxa.